2012
DOI: 10.1118/1.3685582
|View full text |Cite
|
Sign up to set email alerts
|

Dose reduction in LDR brachytherapy by implanted prostate gold fiducial markers

Abstract: There is a major local impact of FM present in LDR brachytherapy seed implant dose distributions. Therefore, reduced tumor control could be expected from FM implanted in tumors, although our results are too limited to draw conclusions regarding clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…4,5 Known dose delivery inaccuracies occur due to the presence of metal bodies and their concomitant streaking artifacts in CT images in case of photon or proton beam treatments 7-9 or combinations with low dose rate (LDR) brachytherapy. 6 The presence of the FMs can cause localized dose reductions between the calculated and delivered dose for proton therapy of up to 38% (Ref. 7) or 47%, 8 depending on the marker and the reference consulted.…”
Section: Ivb Comparison Of the Two Igrt Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Known dose delivery inaccuracies occur due to the presence of metal bodies and their concomitant streaking artifacts in CT images in case of photon or proton beam treatments 7-9 or combinations with low dose rate (LDR) brachytherapy. 6 The presence of the FMs can cause localized dose reductions between the calculated and delivered dose for proton therapy of up to 38% (Ref. 7) or 47%, 8 depending on the marker and the reference consulted.…”
Section: Ivb Comparison Of the Two Igrt Techniquesmentioning
confidence: 99%
“…9 In the case where LDR brachytherapy is used as a boost after external beam radiotherapy the dose perturbation can be quite severe with localized brachytherapy dose reductions of 50%. 6 But can US replace the FM workflow? Johnston et al 16 used an earlier research version of the Clarity system with a different workflow than in our study, and they report slightly larger variation between US and FM with a similar number of patients.…”
Section: Ivb Comparison Of the Two Igrt Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of this research was to quantify the effects of calcifications on the dosimetric parameters of low dose rate prostate brachytherapy treatments, which are used to evaluate clinical outcomes inpatient treatments. Previous studies showed that inaccurate modelling of LDR-BT in commercial treatment planning systems can significantly affect the dosimetric outcome of the treatment [11], [12], [13]. A study evaluating the impact of interseed attenuation for I-125 permanent seed implants found that variation in seed density causes reductions in the CTV D 90 value of up to 3% [11].…”
Section: Iintroductionmentioning
confidence: 99%
“…Elas também podem ser utilizadas como terapia primária, adjunta e para tratamento de recidiva de tumores. Há vastas descrições na literatura que demonstram as aplicações das sementes de 125 I no tratamento de diversos tumores, como neoplasias oculares (SANCHEZ, 2006;STANNARD et al, 2002), câncer de fígado (ZHOU et al, 2007), carcinomas pancreáticos (MAAROUF et al, 2002) e principalmente no câncer de próstata (CHIBANI; TODOR, 2005;LANDRY et al, 2012).…”
Section: Aplicações Clínicasunclassified